The Prevention Strategy against the Incidence of Diarrhea in Toddlers through Hygiene of Milk Bottles-Feeding - Bella Putri Lanida; Farapti Farapti (Jurnal Berkala Epidemiologi, 2018)
Background: Diarrhea is the fourth highest cause of death among children under five years. Interestingly, the most common causes of diarrheal diseases in toddlers is an unhygienic milk bottles-feeding. Purpose: This study aims to analyze how to maintain the hygiene of milk bottles-feeding to prevent the toddler’s diarrhea incidence in Sidotopo Village, Semampir Sub-district, Surabaya City. Methods:  This experiment was an observational analytic study with a cross-sectional study design. The population in this study were mothers who had toddlers in Sidotopo Village, Semampir Sub-district, Surabaya City. In this study, the samples used were 60 toddlers. Accordingly, the research sample was taken by using a simple random sampling method based on Slovin formula calculation. Data collection was conducted from 2 January to 5 February 2018. Further, the data were obtained by questionnaires and in-depth interviews. Data analysis using chi-square test. Results: This present study shows that the technique of maintaining the hygiene of milk bottles can prevent the incidence of diarrhea in toddlers (p < 0.05). The results of the chi-square test showed a significant relationship between the technique of washing hands with soap and without soap on the toddlers’ mother toward the incidence of diarrhea (p = 0.03), but the results of behavior testing on hand washing habits of toddlers’ mothers toward diarrhea incidence showed insignificant results (p = 0.27). Conclusion: There is a technical relationship in maintaining the hygiene of milk bottles-feeding to prevent the occurrence of diarrhea in Sidotopo Village, Semampir Sub-district, Surabaya City.